(untitled) (PANGEEA, 2025)
Tradition of mine in Roşia Montană. Roşia Montană gold mining is done in first century A. H. and continued, without interruption, until today. Because there are many traces of the various stages of mining, the archaeological research began in fifth century. Attended by researchers from Austria, Italy, Germany, Hungary and Romania. Alongside mining, it was very important for researchers the famous "wax tablets" that keeps important information about operation during Roman rule. They have been studied and published since 1975. Currently, about Rosia Montana could say that is an area of great archaeological potential.